2020
DOI: 10.1049/hve2.12040
|View full text |Cite
|
Sign up to set email alerts
|

Research on discharge phenomenon caused by cross‐adsorption of linear insulating fibre and metal dust under DC voltage

Abstract: A large amount of metal dust is often generated during production and operation of Gas Insulated Switchgear/Gas-Insulated Transmission Line, and insulating fibres are very easy to mix in during assembly. The discharge phenomenon induced by these two impurities remains unknown. By setting up a test rig with parallel electrodes, the discharge characteristics of metal dust and linear insulating fibres under the negative DC voltage were studied separately and jointly. The obtained research results indicate some in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…In particular, in most cases the metal particle shows reciprocating motion between the two electrodes. However, when the coaxial electrode is arranged and the negative DC voltage is applied, the linear and flaking particles present the phenomenon of " flying firefly", which not only bump around the high-voltage electrode, but also do not contact the ground electrode [136,137] , as is shown in Figure 34. In addition, for the movement characteristics of metal powder under DC voltage, there is a phenomenon similar to sand storm [138,139] .…”
Section: Metal Particlementioning
confidence: 99%
See 1 more Smart Citation
“…In particular, in most cases the metal particle shows reciprocating motion between the two electrodes. However, when the coaxial electrode is arranged and the negative DC voltage is applied, the linear and flaking particles present the phenomenon of " flying firefly", which not only bump around the high-voltage electrode, but also do not contact the ground electrode [136,137] , as is shown in Figure 34. In addition, for the movement characteristics of metal powder under DC voltage, there is a phenomenon similar to sand storm [138,139] .…”
Section: Metal Particlementioning
confidence: 99%
“…The surface coating of electrode and the addition of particle collector are important means to limit the impact of metal particles on insulation. Many studies have shown that the surface coating has no contribution in moving the particle to the low electric field area, however, it prevents the particle from lift-off by limiting the charge of particle, thus avoiding the disorderly movement of particles in the equipment [139][140][141] . The particle collector is designed with a suitable structure to set a low field area, which can induce the metal particle move into it and limit their motion activity.…”
Section: Metal Particlementioning
confidence: 99%
“…On the other hand, the microstructure and the interaction of the dust can also lead to the distortion of the electric field and induce the surface charge. Due to these two factors, the more area adsorbed by the dust, the more serious the electric field distortion is, resulting in higher electric field and flashover [58].…”
Section: The Influence Of Metal Particlesmentioning
confidence: 99%
“…However, during the production, transportation, assembly, and operation of gas-insulated unit, the metal particles can not be avoided. Notably, there have already been a considerable documents showing that the risk of insulation failure is increased due to the presence of surface charge accumulation and metal particles [5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%